A Simplified Speed Control of Induction Motor based on a Low Cost FPGA - Lotfi charaabi; Ibtihel Jaziri (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper investigates the development of a simplified speed control of induction motor based on indirect field oriented control (FOC). An original PI-P controller is designed to obtain good performances for speed tracking. Controller coefficients are carried out with analytic approach. The algorithm is implemented using a low cost Field Programmable Gate Array (FPGA). The implementation is followed by an efficient design methodology that offers considerable design advantages. The main advantage is the design of reusable and reconfigurable hardware modules for the control of electrical systems. Experimental results carried on a prototyping platform are given to illustrate the efficiency and the benefits of the proposed approach.